Allelic Diversity, Structural Analysis, and Genome-Wide Association Study (GWAS) for Yield and Related Traits Using Unexplored Common Bean (Phaseolus vulgaris L.) Germplasm From Western Himalayas - Mir, Reyazul Rouf; Choudhary, Neeraj; Bawa, Vanya; Jan, Sofora; Singh, Bikram; Bhat, Mohd Ashraf; Paliwal, Rajneesh; Kumar, Ajay; Chitikineni, Annapurna; Thudi, Mahendar; Varshney, Rajeev Kumar (Frontiers in Genetics, 2021)
The north-western Indian Himalayas possesses vast diversity in common bean germplasm due to several years of natural adaptation and farmer’s selection. Systematic efforts have been made for the first time for characterization and use of this huge diversity for identification of genes/QTLs for yield and yield contributing traits in common bean in India. A core set of 96 diverse common bean genotypes were characterized using 91 genome-wide genomic and genic SSR markers. The study of genetic diversity led to the identification of 691 alleles ranging from 2 to 21 with an average of 7.59 alleles/locus. The gene diversity (expected heterozygosity; He) varied from 0.31 to 0.93 with an average of 0.73. As expected, the genic SSR markers detected less allelic diversity than random genomic SSR markers. The traditional clustering and Bayesian clustering (structural analysis) analysis led to clear cut separation of core set of 96 genotypes into two distinct groups based on their gene pools (Mesoamerican and Andean genotypes). Genome-wide association mapping for pods/plant, seeds /pod, seed weight and yield/plant led to the identification of 39 significant marker-trait associations (MTAs) including 15 major, 15 stable, 13 both major and stable MTAs. Out of 39 MTAs detected, 29 were new MTAs reported for the first time; while as remaining 10 MTAs were already identified in earlier studies and therefore declared as validation of earlier results. A set of 7 markers were such, which were found associated with multiple (2-4) different traits. The important MTAs will be used for common bean molecular breeding programs world-wide for enhancing common bean yield.